Impact of Unexplored Data Sources on the Historical Distribution of Three Vector Tick Species in Illinois. Issue 3 (13th December 2019) - Gilliam, Beth; Gronemeyer, Peg; Chakraborty, Sulagna; Winata, Fikriyah; Lyons, Lee Ann; Miller-Hunt, Catherine; Tuten, Holly C; Debosik, Samantha; Freeman, Debbie; O'hara-Ruiz, Marilyn; Mateus-Pinilla, Nohra
Abstract: We updated the Illinois historical (1905–December 2017) distribution and status (not reported, reported or established) maps for Amblyomma americanum (L.) (Acari: Ixodidae), Dermacentor variabilis (Say) (Acari: Ixodidae), and Ixodes scapularis (Say) (Acari: Ixodidae) by compiling publicly available, previously unexplored or newly identified published and unpublished data (untapped data). Primary data sources offered specific tick-level information, followed by secondary and tertiary data sources. For A. americanum, D. variabilis, and I. scapularis, primary data contributed to 90% (4, 045/4, 482), 80% (2, 124/2, 640), and 32% (3, 490/10, 898) tick records vs 10%, 20%, and 68%, respectively from secondary data; primary data updated status in 95% (62/65), 94% (51/54) and in 90% (9/10) of the updated counties for each of these tick species; by 1985 there were tick records in 6%, 68%, and 0% of the counties, compared to 20%, 72%, and 58% by 2004, and 77%, 96%, and 75% of the counties by 2017, respectively for A. americanum, D. variabilis, and I. scapularis . We document the loss of tick records due to unidentified, not cataloged tick collections, unidentified ticks in tick collections, unpublished data or manuscripts without specific county location, and tick-level information, to determine distribution and status. In light of the increase in tick-borne illnesses, updates in historical distributions and status maps help researchers and health officials to identify risk areas for a tick encounter and suggest targeted areas for public outreach and surveillance efforts for ticks and tick-borne diseases. There is a need for a systematic, national vector surveillance program to support research and public health responses to tick expansions and tick-borne diseases.